Ömer Kavur sinemasının edebi kökenleri - Kurt, Hilal (My University, 2009)
ÖZETÖMER KAVUR SİNEMASININ EDEBİ KÖKENLERİÖmer Kavur, edebiyat uyarlamalarıyla ve edebiyatçılarla yaptığı işbirliğiyle özgün bir sinema dili oluşturmuş, Türk sinemasının ender yaratıcı yönetmenlerden biri olmuştur. Yaratıcı yönetmen kimliğini oluştururken ise edebiyattan kuvvet almıştır. Bu çalışmada, edebiyatı tezin merkezine koyarak Ömer Kavur sineması hakkındaki araştırmalara yeni bir bakış açısı kazandırmak amaçlanmıştır. Ömer Kavur sinemasının genel hatlarını anlattığımız “Ömer Kavur Sinemasına Genel Bir Bakış” bölümünün ardından, Ömer Kavur filmleri; “Doğrudan Eser Uyarlamaları”, “Edebiyatçılarla Ortak Senaryo Çalışmaları” ve “Doğrudan Edebiyatla İlişkisi Olmayan Çalışmaları” olmak üzere toplam dört ana başlık altında toplanarak irdelenmiştir. Söz konusu yazarların edebi kişiliği, eserlerinin edebi niteliği, sinemaya senaryo, zaman ve mekân bakımından aktarımı ve edebiyatçılarla ortak çalışmaların Ömer Kavur’un özgün anlatımındaki yeri alt başlıklar halinde incelenmiştir. Çalışmamızda, Ömer Kavur’un içsel bir bağ kurarak çalıştığı edebiyatçıların ve yaptığı edebiyat uyarlamalarının onun sanatsal duruşuna ve onu yaratıcı yönetmen yapan sinema anlayışına katkıda bulunduğu sonucuna varılmıştır. Ömer Kavur’un özgün eserleri bile edebiyattan beslenmiştir.

Ömer Kavur, with his adaptations of literature and his collaboration with literati, has created an original cinema language and has become one of the rare creative directors of Turkish cinema. He took power from literature while creating his creative director identity. In this study, it is aimed to give a new perspective to the researches about Ömer Kavur cinema by putting literature at the center of the thesis. Following the “Overview of Ömer Kavur Cinema” section where we talk about the general lines of Ömer Kavur cinema, Ömer Kavur films; it is gathered and examined under four main headings in the wind Direct Work Adaptations, Common Scenario Work with Literati and Works Not directly Related to Literature. The literary personality of these authors, the literary quality of their works, the transfer to cinema in terms of screenplay, time and space, and the place of joint works with literary writers in Ömer Kavur's original narration are examined under sub-headings. In our study, it was concluded that the literary works of Ömer Kavur, who established an internal connection, and his adaptations of literature contributed to his artistic stance and his understanding of cinema which made him a creative director. Even the original works of Ömer Kavur are nourished by literature.
Keywords: Adaptation of Literature; Edebiyat; Literature; Motion pictures; Ömer Kavur Sineması; Sinema; Turkish Cinema; Türk Sineması Ömer Kavur’s Films; Uyarlama